Ocorrência de Sarasinula marginata (Mollusca: Soleolifera) em Belo Horizonte, MG, Brasil Occurrence of Sarasinula marginata (Mollusca: Soleolifera) in Belo Horiozonte, MG, Brazil - Lais Clark Lima; Cecília Pereira de Souza (Universidade de São Paulo, 1989)
The occurrence of Sarasinula marginata, a possible intermediate host of Angiostrongylus costaricensis, in the city of Belo Horizonte, MG, Brazil, is reported on.